SELF-HEALING MECHANISM BASED ON FAULT MANAGEMENT FOR SMART-GRID DEVELOPMENT ON 20kV SPINDLE NETWORKS TO IMPROVE DISTRIBUTION SYSTEM RELIABILITY AT PLN UID JAKARTA-INDONESIA - Nurwahono, Lugito; Sudiarto, Budi (Asosiasi Dosen Muda Indonesia, 2024)
This study aim is to study for the development of smart grid with the implementation of network automation in the spindle system to improve reliability, revenue and customer experience in the priority areas of PLN UID Jakarta. The addition of new substations has an impact on the reconfiguration changes and the addition of new networks in the context of loading feeders and causing the topology of the distribution network to be increasingly complex and impure spindle systems, in addition to the jammed condition of Jakarta also has an impact on the longer time in investigating disturbances, as well as the limited investment budget of PLN has not supported the installation of new keypoints in all distribution substations. This research was carried out by system modeling in the SCADA Distribution Management System for N-1 contingency and a simulation of the Self-Healing Mechanism test based on static and dynamic data parameters in real-time according to the Load Flow and Load Forecast in the SCADA systems. Evaluation of technical and financial feasibility as a smart feeder design that will be implemented in the spindle system, on the other hand, it is expected to be a Distribution Grid Management design that is feasible to be implemented in the 20kV Spindle system as an alternative to Zero Down Time to accelerate the recovery time of distribution disruptions and improve reliability performance in controlling the operation of the distribution system at PLN UID Jakarta.